PENGELOLAAN MANAJEMEN USAHA MELALUI PELATIHAN KEWIRAUSAHAAN (Studi kasus di Pusat Kegiatan Belajar Masyarakat (PKBM ) “KARYA ANAK BANGSA INSTITUTE” Nagori Simanabun Kabupaten Simalungun) - Marto Silalahi; Parlin Dony Sipayung; Sudung Simatupang (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
In the development of entrepreneurship, training is needed whose purpose is to make the ability of entrepreneurs to become skilled. The results of the service carried out on entrepreneurship training participants with the aim of being skilled in nailing business management carried out by the PKBM research "Karya Anak Bangsa Institute" Nagori Simanabun Simalungun Regency with 15 entrepreneurship training participants. The findings from the results of the service by giving questionnaires to the trainees to see the benefits obtained were found from the training participants that entrepreneurship training provided good and positive results for business management. during the Covid-19 pandemic, especially for high school education levels because it adds experience, understanding, skills and provides opportunities to open your own business in the future and in the future establish cooperative relationships with other related business organizations.